Haloalkane Dehalogenases From Marine Organisms - Kunka, Antonin; Damborsky, Jiri; Prokop, Zbynek (Methods in enzymology, 2018)
Haloalkane dehalogenases degrade halogenated compounds to corresponding alcohols by a hydrolytic mechanism. These enzymes are being intensively investigated as model systems in experimental and in silico studies of enzyme mechanism and evolution, but also hold importance as useful biocatalysts for a number of biotechnological applications. Haloalkane dehalogenases originate from various organisms including bacteria (degraders, symbionts, or pathogens), eukaryotes, and archaea. Several members of this enzyme family have been found in marine organisms. The marine environment represents a good source of enzymes with novel properties, because of its diverse living conditions. A number of novel dehalogenases isolated from marine environments show interesting characteristics such as high activity, unusually broad substrate specificity, stability, or selectivity. In this chapter, the overview of haloalkane dehalogenases from marine organisms is presented and their characteristics are summarized together with an overview of the methods for their identification and biochemical characterization.
Keywords: technologie zelené chemie; alkany; Biocatalysis; Haloalkane dehalogenases; Enzyme Assays; vodní organismy; Green Chemistry Technology; Stability; biotechnologie; Environmental pollutants; Biocatalyst; Hydrolases; Marine environment; Alkanes; hydrolasy; Aldehydes; aldehydy; substrátová specifita; halogeny; Aquatic Organisms; Biotechnology; Halogens; Substrate Specificity; Degradation; Activity; biokatalýza; Selectivity; enzymatické testy